2021
DOI: 10.3390/insects12040309
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Susceptibility to Commercial Insecticides among Populations of the Lesser Mealworm Alphitobius diaperinus Collected from Poultry Houses in France

Abstract: The control of insect pests often relies on the recurrent application of insecticides. This is the case for the lesser mealworm, Alphitobius diaperinus, an invasive beetle infesting poultry farms. There is evidence that A. diaperinus can develop resistance to several insecticides. Evaluation of such resistance has never been conducted in France, despite the beetle’s presence since the 1970s. We assess insecticide susceptibility in 10 populations from French poultry farms and compare patterns with two susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
(34 reference statements)
1
2
0
2
Order By: Relevance
“…It must be highlighted that the results of this study may be limited to the particular LMW strain that was used in these experiments. Several studies have found significant interpopulation variation in susceptibility of LMW, collected from poultry farms, to a variety of pesticides, including the substances imidacloprid, spinosad, and cypermethrin which significantly affected LMW larvae in this study (Hickmann et al, 2018;Renault and Colinet, 2021;Singh and Johnson, 2015). Resistance to the pesticides reported in the latter studies correlated to long-term exposure of populations to sub-lethal doses.…”
Section: Discussionsupporting
confidence: 55%
“…It must be highlighted that the results of this study may be limited to the particular LMW strain that was used in these experiments. Several studies have found significant interpopulation variation in susceptibility of LMW, collected from poultry farms, to a variety of pesticides, including the substances imidacloprid, spinosad, and cypermethrin which significantly affected LMW larvae in this study (Hickmann et al, 2018;Renault and Colinet, 2021;Singh and Johnson, 2015). Resistance to the pesticides reported in the latter studies correlated to long-term exposure of populations to sub-lethal doses.…”
Section: Discussionsupporting
confidence: 55%
“…This species is a cosmopolitan pest that infests stored grains, poultry, and other animal products (Aalbu et al, 2002). It is considered a major pest in poultry farms world-wide and is known to cause significant economic losses due to damage to poultry feed and disease transmission (Renault and Colinet, 2021). This part of the review will discuss the bioecology of A. diaperinus.…”
Section: Bioecology Of Alphitobius Diaperinusmentioning
confidence: 99%
“…Bahkan larva A. diaperinus memiliki kemampuan menggerogoti celah-celah bangunan dan dinding kandang ketika mereka memasuki fase pupasi (Dinev, 2013). A. diaperinus yang termakan oleh ayam dapat mengakibatkan stres gizi karena terbatasnya kemampuan unggas mencerna zat kitin serangga (Renault & Colinet, 2021). A. diaperinus juga merupakan vektor virus Avian leucosis dan dapat menjadi inang bagi bakteri dan jamur penyebab penyakit unggas seperti Escherichia coli, Salmonella enterica, S. typhimurium, Campylobacter jejuni (Hazeleger et al, 2008;Agabou & Alloui, 2010).…”
Section: Pendahuluanunclassified
“…Penggunaan insektisida tidak dapat dipungkiri telah banyak menimbulkan berbagai permasalahan, antara lain meninggalkan residu yang berbahaya terhadap lingkungan dan kesehatan manusia, harga insektisida sintetik fluktuatif (Salaki et al, 2012), menimbulkan efek berbahaya terhadap organisme non-target (As'ad et al, 2019), serta timbulnya resistensi hama terhadap pestisida (Utami et al, 2017). Peneliti terdahulu juga telah membuktikan bahwa populasi A. diaperinus dapat mengembangkan resistensi terhadap insektisida berbasis piretroid, bifenthrin, cyfluthrin, imidakloprid, permetrin, atau tetraklorvinfos (Renault & Colinet, 2021;Lyons et al, 2017;Lambkin & Furlong, 2014). Banyaknya permasalahan akibat penggunaan insektisida sintetis tersebut, telah mendorong banyak peneliti berupaya menemukan alternatif insektisida alami (selanjutnya digunakan istilah bioinsektisida) yang lebih ramah lingkungan, antara lain pemanfaatan senyawa aktif dari tanaman.…”
Section: Pendahuluanunclassified